Contributions of marine area-based management tools to the UN sustainable development goals. (1st January 2022) - Gissi, Elena; Maes, Frank; Kyriazi, Zacharoula; Ruiz-Frau, Ana; Santos, Catarina Frazão; Neumann, Barbara; Quintela, Adriano; Alves, Fátima L.; Borg, Simone; Chen, Wenting; da Luz Fernandes, Maria; Hadjimichael, Maria; et al.
Abstract: Area-Based Management Tools (ABMTs) are spatial instruments for conservation and managing different forms of ocean use. A multitude of ABMTs exists in marine areas within and beyond national jurisdiction, ranging from tools for the regulation of specific human activities (e.g. fisheries, shipping, or mining) to cross-sectoral tools (e.g. such as marine protected areas, MPAs, and marine spatial planning, MSP). By applying expert elicitation and reviewing scientific and grey literature we evaluate the contribution of ABMTs to sustainable development goals (SDGs) as set out under the United Nations 2030 Agenda for Sustainable Development, including for SDG 14 that directly addresses the conservation and sustainable use of oceans, seas, and marine resources. We find that fisheries-related and conservation-related ABMTs, and MSP offer the greatest potential contributions to SDG 14 and to SDGs in general. Moreover, there is high complementarity and synergy among different ABMTs for most SDG 14 targets and other SDGs, with the exception of SDG target 14.6 Prohibit fisheries subsidies and SDG 7 Affordable and clean energy . We find that some ABMTs contribute directly to goal attainment, while others contribute in more nuanced or even unexpected ways. Furthermore, context-specific factors that relate to political and legal factors, enforceability, transparency, governance structure, and inclusivity are crucial for unlocking the full potential of ABMTs of attaining multiple SDGs, as shown through examples. The major challenge to face in the next decade is ensuring durable and equitable outcomes from ABMT implementation by coordinating ABMT initiatives established by different organisations and responsible authorities. It is also critical that outcomes are monitored and evaluated across environmental, social, economic, governance, and health dimensions, with indicators addressing management effectiveness and not only ABMT area coverage. Graphical abstract: Image 1 Highlights: Qualitative assessment of Area-Based Management Tools (ABMT) contribution to SDGs. Expert and literature review provided assessment with evidence from existing cases. We found high complementarity and synergy among different ABMTs for most SDGs. Fishery ABMTs, MPAs and MSP contribute mostly to SDG 14 Life Below Water . All ABMTs can significantly contribute towards SDG 13 Climate action .